An Analysis On The Strategies Used To Translate Idioms With Reference To J.K. Rowling’s Novel Entitled Harry Potter And The Philosopher’s Stone - Nurkasiyati, Nurkasiyati (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
This research is conducted to identify the idiom and its types in JoanneKathleen Rowling’s novel entitled Harry Potter and the Sorcerer’s Stone as wellas strategies used to translate them in the translation versionThe data of this descriptive qualitative research are idiomatic expressionsfound in the novel and its translation in Indonesian language. Documentationis used to collect the data. The data of this research are phrases or sentencesthat contain idiomatic expressions. Meanwhile, content analysis method isapplied for analyzing data in relation to their contexts. The result of this research shows that 140 idioms in 13 types were found in theEnglish novel from chapter 15 to chapter 17. Those thirteen types are phrasalverb (61.43%), prepositional phrase (13.57%), semi-opaque idiom (7.86%), noun phrase (5%), clause idiom (4.29%), idiom of comparison (2.86%), miscellaneous (1.43%), proverb (0.71%), adverb phrase (0.71%), adjectivephrase (0.71%), idiomatic pairs (0.71%), and simile (0.71%). Furthermore, there are three translation strategies used by the translator. Theyare translation using an idiom of similar meaning but dissimilar form, paraphrase, and omission. The researcher found that paraphrase is thehighest number with 134 idioms (95.7%). The second strategy is translation byusing an idiom of similar meaning but dissimilar form with 5 idioms (3.59%). Theless strategy used by the translator is translation by omission with only oneidiom (0.71%). It can be concluded that paraphrase is the most preferredstrategy used by the translator. It was used because she wants to deliver themessage of the text as natural as possible by using the most equivalentmeaning of the idiom in Indonesian